2016
DOI: 10.18632/oncotarget.13217
|View full text |Cite
|
Sign up to set email alerts
|

The genes slyA, STM3120 and htrA are required for the anticancer ability of VNP20009

Abstract: VNP20009 is a very effective anti-cancer agent and can specifically target tumors and inhibit tumor growth. It was assumed that the tumor targeting ability of VNP20009 correlated to its anticancer capacity. However, our observation contradicted to this assumption. Three VNP20009 mutant strains ( ΔslyA , ΔSTM3120 and ΔhtrA ) with reduced fitness in normal tissues and unchanged fitness in tumors partially or completely lost their anti-cancer ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
(42 reference statements)
1
12
0
1
Order By: Relevance
“…Our previous studies found that ΔhtrA with impaired oxidative stress resistance can not engage in normal replication within macrophages (Zhang et al . ), because HtrA is a stress protein for degrading the damaged and misfolded proteins (Mutunga et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies found that ΔhtrA with impaired oxidative stress resistance can not engage in normal replication within macrophages (Zhang et al . ), because HtrA is a stress protein for degrading the damaged and misfolded proteins (Mutunga et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that ΔhtrA exhibited therapeutic potentials with reduced colonization in normal organs and unchanged colonization in tumours (Zhang et al . ). Through systematic comparative toxicity and antitumour effect of VNP20009 and its mutant ΔhtrA in immunodeficient mice, we tried to provide preclinical data on tumour‐targeting Salmonella therapy.…”
Section: Introductionmentioning
confidence: 97%
“…In addition to the intrinsic antitumor effects, bacterial infection induces innate as well as adaptive immune responses against both tumor-colonizing bacteria and the tumor cells 46-48,52,55-59 . The host immune responses are more critical for the antitumor effects of bacteria such as Salmonella that are not sufficiently cytotoxic to tumor cells 55,60 . Numerous studies have suggested that both bacterium-intrinsic and host immune mechanisms are involved in tumor destruction (FIG.…”
Section: Live Tumor-targeting Bacteriamentioning
confidence: 99%
“…Our preliminary study identified attenuated Salmonella VNP20009 as an effective plasmid delivery vector (Cheng et al, 2014 ) as well as a heterologous protein expression vector (Liu et al, 2015 ), and our previous research also successfully achieved a schistosome vaccine candidate based on an attenuated Salmonella vector (Chen et al, 2011 ). We also obtained an attenuated Salmonella mutant, Δ htrA ‐VNP, with a good safety profile, which has significantly reduced splenic and hepatic virulence compared with wild‐type VNP, making it suitable for vaccine or drug delivery vectors (Zhang et al, 2016 ). Here, we attempted to engineer Δ htrA ‐VNP as the SARS‐CoV‐2 antigen expression vector.…”
Section: Introductionmentioning
confidence: 99%